The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1074/jbc.m302471200
|View full text |Cite
|
Sign up to set email alerts
|

The C2-like β-Barrel Domain Mediates the Ca2+-dependent Resistance of 5-Lipoxygenase Activity Against Inhibition by Glutathione Peroxidase-1

Abstract: Recently, we reported that in crude enzyme preparations, a monocyte-derived soluble protein (M-DSP) renders 5-lipoxygenase (5-LO) activity Ca 2؉ -dependent. Here we provide evidence that this M-DSP is glutathione peroxidase (GPx)-1. Thus, the inhibitory effect of the M-DSP on 5-LO could be overcome by the GPx-1 inhibitor mercaptosuccinate and by the broad spectrum GPx inhibitor iodoacetate, as well as by addition of 13(S)-hydroperoxy-9Z,11E-octadecadienoic acid (13(S)-HPODE). Also, the chromatographic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
3
24
0
Order By: Relevance
“…1E). In our previous report (26) we suggest that stimulation of 5-LO by Ca 2ϩ is because of an increased affinity toward activating LOOH. In fact, the addition of 5-HPETE to PMNL-S100 concentration-dependently up-regulated the LTA 4 synthase activity of 5-LO in the absence of Ca 2ϩ or OAG (Fig.…”
Section: Oag Stimulates 5-lo In Vitro In the Absence Of Camentioning
confidence: 99%
See 3 more Smart Citations
“…1E). In our previous report (26) we suggest that stimulation of 5-LO by Ca 2ϩ is because of an increased affinity toward activating LOOH. In fact, the addition of 5-HPETE to PMNL-S100 concentration-dependently up-regulated the LTA 4 synthase activity of 5-LO in the absence of Ca 2ϩ or OAG (Fig.…”
Section: Oag Stimulates 5-lo In Vitro In the Absence Of Camentioning
confidence: 99%
“…OAG Renders 5-LO Activity Resistant against GPx-It was found that Ca 2ϩ renders 5-LO activity resistant against inhibition by GPx-1 (26). We attempted to investigate whether OAG could mimic the effect of Ca 2ϩ , rendering 5-LO activity GPx-resistant.…”
Section: Oag Stimulates 5-lo In Vitro In the Absence Of Camentioning
confidence: 99%
See 2 more Smart Citations
“…Ca 2+ binds to the regulatory C2-like domain, mediates binding of 5-LO to PC-containing membranes or lipid vesicles, lowers the K m value for AA as substrate, and decreases the requirement of 5-LO for activating LOOH, which altogether potently enhances 5-LO catalysis in vitro [21], [24], [31]. In the cell, Ca 2+ facilitates 5-LO association with the nuclear membrane and protects 5-LO activity against GPx activity [48]. Hence, it is reasonable to assume that natural compounds that chelate Ca 2+ or interfere with Ca 2+ mobilization (i. e., by blocking channels, or interaction with signaling molecules such as PLC, IP3 receptors) prevent activation of 5-LO without inhibiting the enzyme directly.…”
Section: Activation Pathways Of 5-lo In the Cellmentioning
confidence: 99%